Protein Synthesis Initiation in Eukaryotic Cells - Merrick, William C. (Cold Spring Harb Perspect Biol, 2018)
This review summarizes our current understanding of the major pathway for the initiation phase of protein synthesis in eukaryotic cells, with a focus on recent advances. We describe the major scanning or messenger RNA (mRNA) m(7)G cap-dependent mechanism, which is a highly coordinated and stepwise regulated process that requires the combined action of at least 12 distinct translation factors with initiator transfer RNA (tRNA), ribosomes, and mRNAs. We limit our review to studies involving either mammalian or budding yeast cells and factors, as these represent the two best-studied experimental systems, and only include a reference to other organisms where particular insight has been gained. We close with a brief description of what we feel are some of the major unknowns in eukaryotic initiation.